2020
DOI: 10.1055/a-1108-3004
|View full text |Cite
|
Sign up to set email alerts
|

Großer Pneumothorax unter CPAP-Therapie beim Schlafapnoepatienten ohne vorbekannte Lungen- und Thoraxerkrankungen – ein Fallbericht

Abstract: ZusammenfassungEine CPAP-Therapie ist die häufigste Behandlungsform der obstruktiven Schlafapnoe.Schwerwiegende Komplikation dieser Behandlung sind sehr selten. Pneumothorax als Lungen-Barotrauma unter der CPAP-Therapie wird in Einzelfallberichten und ausschließlich bei vorbestehenden Lungen- und Thoraxerkrankungen beschrieben.Ein 68-jähriger, pulmonal nicht vorerkrankter Schlafapnoe-Patient mit einer langjährig etablierten CPAP-Therapie wird nach einem heftigen thorakalen Schmerzereignis mit anhaltender Luftn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…This suggests that spontaneous pneumothorax may be related to the total height at the time of onset, and that spontaneous pneumothorax may occur even when standing in high places at lower heights. Previous case reports of sleep apnea syndrome combined with spontaneous pneumothorax [22] , this study found limited evidence of a causal relationship between sleep apnea syndrome and spontaneous pneumothorax, but snoring was causally associated with an increased risk of spontaneous pneumothorax. There are previous case reports of secondary school students who developed pneumothorax after blowing hard during a physical spirometry test [23] , and the present study also found that first second expiratory volume with exertion was positively associated with the risk of spontaneous pneumothorax, whereas expiratory spirometry was negatively associated with the risk.…”
Section: Discusscontrasting
confidence: 88%
“…This suggests that spontaneous pneumothorax may be related to the total height at the time of onset, and that spontaneous pneumothorax may occur even when standing in high places at lower heights. Previous case reports of sleep apnea syndrome combined with spontaneous pneumothorax [22] , this study found limited evidence of a causal relationship between sleep apnea syndrome and spontaneous pneumothorax, but snoring was causally associated with an increased risk of spontaneous pneumothorax. There are previous case reports of secondary school students who developed pneumothorax after blowing hard during a physical spirometry test [23] , and the present study also found that first second expiratory volume with exertion was positively associated with the risk of spontaneous pneumothorax, whereas expiratory spirometry was negatively associated with the risk.…”
Section: Discusscontrasting
confidence: 88%
“…There is a report in which a 68-yearold patient on CPAP for many years for OSA presented with spontaneous pneumothorax and basal bullous emphysema. 12 Another report described recurrent pneumothorax after five years of NPPV, along with blebs that had not previously been identified on prior chest radiograph (no CT was available). 13 It is possible that barotrauma from high pressures could lead to bulla neogenesis, although set auto CPAP pressures are typically lower than levels suspected to cause barotrauma.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary barotrauma can occur as a result of a continuous increase in pressure, which causes hyperinflation and rupture of alveoli in CPAP-treated patients [4]. In particular, patients with emphysematous lungs have a higher likelihood of developing pneumothorax because their function is already impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma-related side effects can occur in CPAP treatment due to the high pressure to which patients are exposed. In rare cases, CPAP can cause pneumothorax, pneumomediastinum, and lung herniation associated with high pressure in the thorax [4][5][6][7]. These complications can occur in any patient, but in patients with lung disease, they are both more likely to occur and more life-threatening.…”
Section: Introductionmentioning
confidence: 99%